On the structuralist view of inflation in some Latin American countries: A reassessment - Bernhard Fischer; Thomas Mayer (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1980)
Comparing inflation rates internationally, one finds a number of Latin American countries in the lead. Therefore, when investigating inflation in LDCs, it has become common practice to refer to these countries as prime examples. Mainly two theories have been put forward to explain Latin American inflation: the monetarist and structuralist hypotheses. While in the monetarist theory aggregate excess demand resulting from an excess supply of money is regarded as the only cause of inflation, the structuralist theory ascribes inflation also to the composition of demand for products and services accompanied by inflexibilities in the productive structure. The purpose of this paper is to give further empirical evidence for the structuralist view of inflation in six selected Latin American countries: Bolivia, Brazil, Chile, Colombia, Ecuador and Peru. They have all been highly prone to inflation in the past. First, we outline the theoretical background of our investigation. Subsequently, empirical tests of the hypotheses are provided. Finally, we draw some conclusions from our study and relate the findings to the discussion of the harmful effects of export instability in LDCs.
Keywords: 330